Optimalisasi Pembelajaran Aqidah Akhlak dalam Mempengaruhi Perilaku Peserta Didik di Madrasah Aliyah - Muhammad Chairullah Tamiran; Apriliyanus Pratama Rakhamadi; Anugrah lestari (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
This research examines the influence of learning moral beliefs on student behavior at MAN 1 Gorontalo Regency. Due to the increase in juvenile delinquency due to changes in social norms. So this research wants to identify the extent to which learning aqidah morals contributes to student behavior. The research used a quantitative approach with a sample of 83 students taken using the Slovin method. Data was collected through a questionnaire which was tested for validity and reliability. Data analysis was carried out using descriptive statistics and simple linear regression. The results of the research show that the calculated F value is 0.997, which is smaller than the F table of 3.96 and the significance level is 0.321 which is above 0.05, that there is no influence of learning moral beliefs on student behavior. External factors such as family environment, peers and the media are more influential in shaping their behavior.